PELAKSANAAN PELATIHAN DAN PENGEMBANGAN PADA PUSAT PELATIHAN PERTANIAN PEDESAAN SWADAYA (P4S) KARYA NYATA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Ahmad Akbar; Zaili Rusli. SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Training and development is an activity to improve the quality of human resources in achieving mastery of skills, knowledge, and abilities. The formulation of the problem in this research is how the "Implementation of Training and Development at the Center for Agricultural Training Rural Governmental of Real Kubang Jaya Subdistrict Siak Hulu and Kampar Factors affecting Implementation of Training and Development at the Center for Agricultural Training Rural Governmental of real Kubang Jaya Subdistrict Siak Hulu Kampar "with the aim of research to" Knowing Implementation of Training and Development at the Center for Agricultural Training Rural Governmental of real Kubang Jaya Subdistrict Siak Hulu and Kampar Knowing factors affecting Implementation of Training and Development at the Center Governmental Rural Agricultural training of Real Kubang Jaya Subdistrict Siak Hulu and Kampar". The method used is descriptive qualitative method, the analysis that seeks to provide a detailed description based on the fact that some in the field regarding the implementation of training and development, especially on Governmental Rural Agricultural Training Centre of Real Kubang Jaya. The data used in this study consisted of (Assessment of Needs, Objectives, Materials Program, Principles of Learning), and secondary (Cost Effectiveness, Accuracy and Compatibility Facility, Capabilities and Preferences Participant, Capabilities and Preferences Instructor). Data collection techniques include: observation, interviews, and a review of documentation. Involving thirteen persons consisting of one head of one person BPPKP field P4S P4S chairman of the public relations and promotions section P4S three instructors from three participants three alumni and one P4S environmental community.The results of this research is Implementation of Training and Development at the Center for Agricultural Training Rural Governmental of Real Kubang Jaya Subdistrict Siak Hulu and Kampar yet well run. This is because all of the participants have had training in real work P4S Kubang Jaya have increase in knowledge, skills and abilities. But such knowledge is only possessed a moment, except for the capital gain from the government and can apply their knowledge.Keywords: Training, Development, Agricultural Training Center of rural